Bronze alloys with tin surface sites for selective electrochemical reduction of CO2. Issue 99 (27th November 2018) - Vasileff, Anthony; Xu, Chaochen; Ge, Lei; Zheng, Yao; Qiao, Shi-Zhang
Abstract : Low concentration tin bronze alloys show high selectivity for CO2 electroreduction to CO, while high concentration tin bronze alloys show high selectivity for formate. Abstract : Low concentration tin bronze alloys show high selectivity for CO2 electroreduction to CO, while high concentration tin bronze alloys show high selectivity for formate. The tin surface sites appear to control selectivity by influencing the binding characteristics toward the first reaction intermediate on copper-based alloys.